PENGARUH MODEL PEMBELAJARAN STUDENT TEAM ACHIEVEMENT DIVISIONS (STAD) TERHADAP KEMAMPUAN MENGANALISIS STRUKTUR TEKS NEGOSIASI KELAS X SMA - Sari, Rafika Muspita (Fakultas Keguruan dan Ilmu Pendidikan Univesitas Dharmas Indonesia, 2023)
The purpose of this study is to determine whether there is an influence in the application of the Student Teams Achievement Division (STAD) learning model on the Ability to Analyze Negotiation Text Structures for Class X SMA Negeri 1 Lima Puluh . The type of this research is experimental research with the form of experimental design, amely True-experimental design type post test only control design. In class Nese Experiment class using the Student Teams Achievement Division (STAD) learning method and class X3 as the control class using the conventional method. Post-test was obtaned with an average result of 80 for the Experiment class and 61,9 the control class. The results of the to calculation that have been obtaned show at ts value is obtaned, then the t table is consulted at the 5% and 1% level with dk = (NI+N2)-2 = (36+36)-2-70. In tablet with dk = 70, there is a significant level of 5% = 2.00 and a significant level of 1% = 2.65 because tcount (o) is greater than label (11), which is a significant level of 5% (6.93>2, 00). Then the significance level of 1% (6.93> 2.65), then the null hypothesis (Ho) is rejected and the alternative hypothesis (Ha) is accepted.